1997
DOI: 10.1088/0953-4075/30/7/003
|View full text |Cite
|
Sign up to set email alerts
|

Hot nanoplasmas from intense laser irradiation of argon clusters

Abstract: Argon ions with charge states of at least up to q = 9 are produced with 10 14 W cm −2 , 30 ps laser light pulses at 1064 nm from neutral Ar n clusters, whereas only Ar 3+ can be produced from monomers. Irradiation of cluster targets leads to ions with remarkably high kinetic energies exceeding 4.8 keV, depending on the ion charge state. The experimental results are understood in terms of cluster-sized nanoplasmas with internal electron temperatures of approximately 7 × 10 6 K which are heated by collisional el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 20 publications
2
47
0
1
Order By: Relevance
“…One manifestation is the up-conversion of the incident infra-red laser into keV X-ray photons in rare-gas clusters, which takes place with a relatively high efficiency providing large X-ray yields just like in solids, yet is relatively debris-free, a property shared with gas targets [1]. Similar behavior has been observed for the emission of energetic electrons [2] or highly charged ions [3], thus making the interaction of intense short and ultra-short laser pulses with clusters a topic of considerable interest [4; 5].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…One manifestation is the up-conversion of the incident infra-red laser into keV X-ray photons in rare-gas clusters, which takes place with a relatively high efficiency providing large X-ray yields just like in solids, yet is relatively debris-free, a property shared with gas targets [1]. Similar behavior has been observed for the emission of energetic electrons [2] or highly charged ions [3], thus making the interaction of intense short and ultra-short laser pulses with clusters a topic of considerable interest [4; 5].…”
Section: Introductionmentioning
confidence: 69%
“…One manifestation is the up-conversion of the incident infra-red laser into keV X-ray photons in rare-gas clusters, which takes place with a relatively high efficiency providing large X-ray yields just like in solids, yet is relatively debris-free, a property shared with gas targets [1]. Similar behavior has been observed for the emission of energetic electrons [2] or highly charged ions [3], thus making the interaction of intense short and ultra-short laser pulses with clusters a topic of considerable interest [4; 5].In a simple picture, the dynamics during the interaction of a strong laser pulse with a cluster can be summarized as follows [6]: the atoms of the cluster are first ionized by the incident laser pulse (inner ionization) and a cold "nano-plasma" of solid density is formed. The quasi-free electrons take part in a collective oscillation driven by the laser field and, moreover, interact with the field of the surrounding particles.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The experiments on laser interactions with atomic clusters have suggested that the laser-cluster interaction is more energetic than that of isolated atoms. Efficient generation of highly-charged atomic ions [1][2][3][4][5], generation of electrons and ions with MeV kinetic energies [4,[6][7][8], and emission of intense X-rays [2,9,10] were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on clusters irradiated by the intense laser pulses have revealed efficient generation of extremely highly charged atomic ions [2][3][4][5][6][7][8] and generation of electrons and ions with MeV kinetic energies [6,7,[9][10][11]. Several other theoretical models have been proposed to explain the mechanism underlying the production of highly charged energetic ions in interaction of atomic clusters with intense laser pulses.…”
Section: Introductionmentioning
confidence: 99%